Open field test for the assessment of anxiety-like behavior in Gnathonemus petersii fish - Horka, Petra; Langova, Veronika; Hubeny, Jan; Vales, Karel; Chrtkova, Ivana; Horacek, Jiri (Frontiers in Behavioral Neuroscience, 2024)
The open field test (OFT) is a basic and most widely used test for investigation in animal studies of the neurobiological basis of anxiety and screening for novel drug targets. Here, we present the results of an OFT for weakly electric fish Gnathonemus petersii. This study aimed to describe the behavioral response of G. petersii exposed to an OFT, simultaneously with an evaluation of electrical organ discharges (EOD), to determine whether any association between EOD and patterns of motor behavior in the OFT exists. Treatment of OFT activity and its temporal patterning was assessed for the whole 6minute trial as well as per-minute distributions of activity using a near-infrared camera and an EOD data acquisition system. Our results demonstrated that the time spent, distance moved, and time of activity were significantly higher in the periphery of the OFT arena. The zone preference pattern over the 6-minute test session showed that G. petersii prefer the outer zone (83.61%) over the center of the arena (16.39%). The motor behavior of fish measured as distance moved, active time, and swim speed were correlated with the number of EODs; however, no relationship was found between EOD and acceleration.